2013
DOI: 10.1017/jse.2013.2
|View full text |Cite
|
Sign up to set email alerts
|

Tic Disorders and Learning Disability: Clinical Characteristics, Cognitive Performance and Comorbidity

Abstract: Tics are involuntary movements or sounds. Tourette syndrome is one of a family of tic disorders that affect around 1% of the population but which remains underrecognised in the community. In paediatric special education learning disability classes, the prevalence of individuals with tic disorders is around 20-45% -higher still in special education emotional/behavioural classes. Given the high rates of individuals with tic disorders in special education settings, as well as the unique challenges of working in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…All of these can lower self-esteem directly or have consequences that may lead to poorer psychosocial functioning and QoL. For example, tics and comorbid ADHD may interact to create a vicious cycle of distractibility and inability to focus, due to both the efforts in trying to control the tics and due to inattention of ADHD; similarly, tics and comorbid severe obsessive compulsive disorder (OCD) may render an individual to check repeatedly, striving for perfection, and thus unable to finish school or office work ( 2 ). This may limit academic progress, while at the same time, negatively affecting the social outcomes and opportunities due to lack of education and under or unemployment.…”
Section: The Impact Of Comorbidities and Coexistent Psychopathologiesmentioning
confidence: 99%
“…All of these can lower self-esteem directly or have consequences that may lead to poorer psychosocial functioning and QoL. For example, tics and comorbid ADHD may interact to create a vicious cycle of distractibility and inability to focus, due to both the efforts in trying to control the tics and due to inattention of ADHD; similarly, tics and comorbid severe obsessive compulsive disorder (OCD) may render an individual to check repeatedly, striving for perfection, and thus unable to finish school or office work ( 2 ). This may limit academic progress, while at the same time, negatively affecting the social outcomes and opportunities due to lack of education and under or unemployment.…”
Section: The Impact Of Comorbidities and Coexistent Psychopathologiesmentioning
confidence: 99%
“…Learning difficulties in TS have been studied as the result of the negative impact of tics on daily functioning. In special education and learning disability classes, the prevalence of tic disorders is approximately 10 times higher than in the general population [ 231 ]. In many cases, learning difficulties are associated with delays in learning skills, poor attention, hyperactivity, or other behavioral and/or psychological disorders [ 229 , 230 , 232 ].…”
Section: A Review Of Neuropsychological Functioning In Tsmentioning
confidence: 99%
“…The YGTSS is a semi-structured clinician rated scale assessing tic severity based on the presence of tics in the previous week. Tics were classified as “simple” if it involved only a single group of muscles or a simple vocal/phonic sound 3. It is to be noted that invariably all patients who had complex tics also had simple tics.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the core clinical features that are integral to TS, a wide range of other behavioral, emotional, and psychiatric conditions have been reported to occur more commonly in TS as compared to the general population (eg, ADHD in 60% of the TS population as compared to 5%–10% in the general population and OCD in 30%–50% of the TS population as compared to 1%–3% in the general population) and previous studies have also suggested that increased tic severity is associated with increased psychopathology 4,711. Further, TS has been to a lesser extent associated with autism spectrum disorder 3,9,11. A number of co-existent psychopathologies have also been described in TS including anxiety, depression, learning difficulties, personality disorder, impulse control, aggression, oppositional defiant disorder, and conduct disorder 6.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation